2023
DOI: 10.3390/vaccines11071219
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Systemic Humoral Immune Response Induced in Mice by Generalized Modules for Membrane Antigens (GMMA) Is Associated with Affinity Maturation and Isotype Switching

Abstract: Generalized Modules for Membrane Antigens (GMMA) are outer membrane vesicles derived from Gram-negative bacteria that can be used to design affordable subunit vaccines. GMMA have been observed to induce a potent humoral immune response in preclinical and clinical studies. In addition, in preclinical studies, it has been found that GMMA can be exploited as optimal antigen carriers for both protein and saccharide antigens, as they are able to promote the enhancement of the antigen-specific humoral immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
2
0
0
Order By: Relevance
“…When adsorbed on Alhydrogel, serotype specific IgG responses became comparable but GMMA continued to elicit significantly higher SBA titers than glycoconjugates. Higher functionality could be linked to a broader IgG isotype switch observed with GMMA (Piccioli et al, 2023). These results are in agreement with those previously observed comparing Salmonella GMMA and glycoconjugates in mice (Micoli et al, 2018b).…”
Section: Discussionsupporting
confidence: 92%
“…When adsorbed on Alhydrogel, serotype specific IgG responses became comparable but GMMA continued to elicit significantly higher SBA titers than glycoconjugates. Higher functionality could be linked to a broader IgG isotype switch observed with GMMA (Piccioli et al, 2023). These results are in agreement with those previously observed comparing Salmonella GMMA and glycoconjugates in mice (Micoli et al, 2018b).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, we showed that the presence of aluminium salt-based adjuvants reduced the levels of IgG3 induced by GMMA in mice, which had a strong correlation with bactericidal activity (Table 1), and this may be a possible explanation for the observed results. Consistently, we have previously demonstrated in a Meningococcus B model (MenB) that, when immunising mice with GMMA harbouring the antigen factor H-binding protein (fHbp) on the surface, the bactericidal activity mediated by fHbp was increased compared to fHbp alone or fHbp physically mixed with GMMA, and this increase was associated with the higher production of IgG subclasses with superior bactericidal potential against MenB, including IgG3 [35].…”
Section: Discussionsupporting
confidence: 74%